Analisis Mitigasi Risiko Pada Rantai Pasok di PT. ABC dengan Menggunakan Metode House of Risk dan SCOR - Mohammad Sabilarrosyad; Moh. Jufriyanto; Hidayat Hidayat (Universitas Islam Raden Rahmat, Malang, 2024)
The competition in the global industry has shifted towards supply chain competition. Therefore, handling and understanding risks in the supply chain has become very important. The objective of this research is to analyze the risks present in the supply chain flow of PT. ABC and design preventive actions for the prioritized risks. This research utilizes the SCOR analysis and the House of Risk method. After processing, five priority Risk Agents were identified, namely A18, A9, A6, A4, and A5. As a result, eight preventive actions were proposed, including (PA1) Updating work SOPs, (PA2) Implementing a reward and punishment system, (PA3) Building a pre-sedimentation unit, (PA4) Coordinating with various relevant parties, (PA5) Organizing seminars on the importance of maintaining raw water sources for stakeholders and the community, (PA6) Establishing agreements at the beginning of a partnership contract with specific actions in case of errors, (PA7) Calculating Safety Stock, (PA8) Adding backup supplier connections/lines in case the main supplier experiences a shortage of raw materials.